Narrative Reconsiderations of Teaching as Negotiated Curriculum for Social Justice and Equity - Schlein, Candace; Smith, Dianne; Oakley, Charles (Frontiers in Education, 2019)
Curriculum is negotiated in intricate ways through various forms of interactions between teachers and students, among students, or via acts of mentoring. Attending to the details of the experiences and interactions of such negotiations within the construct of narrative deliberation may prove to be illuminating in terms of understanding top-down and bottom-up influences on teaching and learning. In this article, we discuss the findings of a narrative inquiry into Education professors' experiences of these forms of curricular interaction in higher education. We underscore socially just and equitable curriculum development through engagement with teacher education students. We further reflect on mentoring as an outgrowth of teaching that might serve to sustain curriculum negotiation from an equity and social justice vantage.